Abdication of freedom as an exercise of discipleship: Reflexions on 1 Cor 8.1 – 11.1 - Yan, Anderson (Vox Scripturae - Revista Teológica Internacional, 2025)
This essay argues that a careful reading of 1 Cor 8.1 – 11.1 indicates a rhetorical skill, which bridges different themes within an A-B-A structure with the purpose of dealing with the disturbance of the unity of the church caused by the abuse of freedom.
Keywords: Division; Food sacrificed to the idols; Rights of the apostle; Discipleship